Shaping Spoken Accuracy through Oral Corrective Feedback - Tiara Noviarini; Candraning Prihatini (Universitas Muhammadiyah Lampung, 2024)
Spoken accuracy remains a persistent challenge for undergraduate learners of English as a Foreign Language (EFL), particularly in contexts where English is primarily used within the classroom. Although learners may possess adequate grammatical knowledge, difficulties often arise when producing accurate spoken language in real-time interaction. One instructional practice commonly employed to address spoken errors is oral corrective feedback, yet how such feedback functions interactionally to shape spoken accuracy in undergraduate EFL classrooms requires further exploration. This study aims to examine how oral corrective feedback contributes to shaping spoken accuracy through classroom interaction.Adopting a qualitative case study design, the research was conducted in an undergraduate (S1) EFL speaking class at UAI Syeh M involving 20 students. Data were collected through non-participant classroom observation, video recordings of speaking activities, and semi-structured student interviews. The primary unit of analysis was the feedback episode, consisting of a learner’s spoken error, oral corrective feedback provided by the lecturer, and the learner’s subsequent response. The data were analyzed interactionally to identify patterns of oral corrective feedback, forms of student uptake, and their contribution to spoken accuracy. The findings indicate that oral corrective feedback emerges naturally during speaking activities and operates along a continuum from prompt-based strategies to explicit reformulations. Explicit correction was frequently used to address errors that interfered with meaning, while prompt-based feedback such as elicitation and clarification requests encouraged learners to engage cognitively in self-repair. Student uptake manifested in both successful repair and partial responses, reflecting learners’ attention to linguistic form and engagement in the feedback process. Interview data further revealed that learners perceived feedback prompting reflection and self-correction as particularly supportive of their speaking development. Overall, the study highlights oral corrective feedback as an interactional mechanism that shapes spoken accuracy through learner engagement, noticing, and repair. The findings underscore the importance of context-sensitive feedback practices in undergraduate EFL speaking instruction and contribute to a deeper understanding of feedback processes in classroom interaction.